Myasthenia gravis: understanding treatment patterns and direct medical costs in the Czech Republic - Donin, Gleb; Mothejlová, Karla; Horáková, Magda; Vohanka, Stanislav (Orphanet journal of rare diseases, 2024)
BACKGROUND: Myasthenia gravis (MG) is a rare autoimmune disorder with significant clinical implications, including life-threatening myasthenic crises and exacerbations. Understanding real-world treatment patterns, especially associated direct medical costs, is essential for the effective management of healthcare delivery. METHODS: We conducted a descriptive cohort study using health administrative claims data from the Czech Republic covering more than 1,500 prevalent MG patients. Data were analysed for healthcare resource utilization, medication costs, and hospitalization rates related to MG and its complications. RESULTS: Acetylcholine inhibitors and corticosteroids were widely prescribed, with 91.1% and 75.2% of patients receiving them at least once, respectively. Immunosuppressive therapy was given to 45.2% of patients. Myasthenic crises occurred in 2% of patients, with a mean hospitalization cost of 21,020 EUR, while exacerbations occurred in 9.2% of patients, with lower costs (5,951 EUR per hospitalization). Outpatient intravenous immunoglobulin and plasma exchange therapies incurred additional costs of 20,700 EUR and 18,206 EUR per person-year, respectively. The mean total cost per patient-year was 1,271 EUR, with significant cost differences among patients with different treatment patterns. CONCLUSION: This study offers real-world insights into the treatment patterns and associated direct medical costs of MG in the Czech Republic. Myasthenic crises and exacerbations pose considerable cost burdens, while outpatient therapies and common pharmacotherapies are less costly. These findings are vital for healthcare planning, economic evaluation, and resource allocation, potentially leading to enhanced patient care and outcomes.
Keywords: Health Care Costs; Humans; lidé středního věku; Treatment patterns; kohortové studie; Female; Aged; mladý dospělý; dospělí; senioři; lidé; myasthenia gravis; Myasthenia gravis; hospitalizace; Cohort Studies; náklady na zdravotní péči; Adult; ženské pohlaví; Male; Hospitalization; Middle Aged; Direct healthcare costs; Adolescent; Czech Republic; Young Adult; Česká republika; mužské pohlaví; Myasthenia Gravis; mladiství